As percepções das práticas pedagógicas de educação ambiental dos docentes do ensino fundamental I em Brumadinho pós- desastre ambiental - Ana Heloisa Silva e Pires (2023)
Mineral extraction in Brazil tends to neglect environmental preservation and the health of individuals who participate in this process. Since 2015, in Minas Gerais, there have been two disasters resulting from this activity, one in Bento Rodrigues, in the municipality of Mariana MG, and another in Córrego do Feijão, in Brumadinho. The environmental and social consequences of these events are immeasurable. Our question sought to investigate whether the impacts arising from the rupture of the dam in Brumadinho can be perceived in the pedagogical practices of teachers who work in the first cycles of Elementary School and who address Environmental Education. Thus, we investigated whether the Environmental Education practices of Elementary School I teachers who teach in Brumadinho address the environmental and human disaster that occurred in this city and whether the municipality's leaders influence these practices. The objective of this research was to identify and understand the conceptions and knowledge of professors regarding their Environmental Education practices in the post disaster environmental scenario. This qualitative research then intended to investigate teachers who work in Elementary School I who address the theme of Environmental Education in their educational practices in public schools in the city of Brumadinho. Based on semi-structured interviews with teachers and secretariat employees, we noticed that there is little incentive from municipal secretariats for Environmental Education practices. The investigated teachers have environmental concerns, but their EE conceptions oscillate between conservative and pragmatic views. We also understand that the critical and political training of teachers infers a greater approximation to a critical and liberating practice. We note that technical training and specialization in EA is not a condition that allows the execution of a critical education. The EE practices cited by the investigated teachers have their own intentions as a starting point, starting from the teachers' own ideals and initiatives, articulated or not with specific training for EE. We also observed that all teachers stated that they addressed the rupture of the dam and what happened in the city in their EE practices, but we understand that this subject is only mentioned by them and rarely addressed in classes. Although these researched teachers addressed what happened in the city, they stated that they avoid using the dam rupture as a theme in their classes on the grounds that it is a sensitive topic. We observed that mining and the dam rupture influenced and caused an impact on teachers' practices but did not interfere with their EE conceptions and did not influence the development of critical education